(untitled) (JOURNAL OF ADVANCES IN PHYSICS, 2019)
Algebraic Quantum Theory of Consciousness A Solution to the Problem of Quantum Collapse in Systems Having Three Anticommuting Elements ISBN 978-88-255-1707-1, formato 17 x 24 cm, 112 pagine, 14 euro